Pengaruh Pola Asuh Otoriter Orang Tua Terhadap Perilaku Prososial Siswa di Smp Negeri 11 Muaro Jambi - Putri Puspita Sari; Nelyahardi Gutji; Fellicia Ayu Sekonda (Journal on Education, 2023)
Prosocial behavior is an individual action to help others, often without direct benefit to the helper. Students' prosocial behavior can be influenced by parenting styles, one of which is authoritarian parenting. Authoritarian parenting is parenting style of parents who prioritize the formation of students' personalities by setting absolute standards that must be followed, usually balanced with threats or punishment. The same thing also happened in the educational environment of SMP Negeri 11 Muara Jambi where negative student prosocial behavior still occurred, such as students who showed disobedience, did not want to do school work, students who liked to bully their friends and some who liked to get angry. This research uses a quantitative approach with the type of inferential research and is descriptive in nature. The sample in this study were 65 students who described an authoritarian parenting style. The research instrument used was a research questionnaire with a Likert scale. The data analysis used is Descriptive Analysis and Regression Analysis. The results showed that: (1) Authoritarian parenting parents at SMP Negeri 11 Muara Jambi based on indicators of the approach used contained elements of coercion and punishment, parents tended to control children, and children did not have freedom as a whole at a high level with a percentage value of 82.68%; (2) The prosocial behavior of students at SMP Negeri 11 Muara Jambi based on indicators of self-efficacy, altruism, empathy and aggression is at a high level with a percentage of 82.71%; and (3) there is a negative effect on the authoritarian parenting style of students' parents on the prosocial behavior of students at SMP Negeri 11 Muara Jambi with an effect of 52.8%.